Neurophysiological Model of Altered States of Consciousness Induced by Breathing Techniques - Zaccaro, Andrea; Penazzi, Gabriele (Cosmos and History: The Journal of Natural and Social Philosophy, 2019)
This paper is based on recent research on animal and human models related to the physiology of respiration. It aims at building an initial neurophysiological model of breathing practices, in order to explain how these techniques induce altered states of consciousness in humans. Confirming traditional long-term knowledge from the East, we suggest that air-induced mechanical nasal stimulation is crucial for reaching meditative states of consciousness during breathing practices. In a time of rapidly emerging data about higher-order functions of respiration, we speculate that the fine-tuned modulation driven by breathing on the interaction between brain and peripheric systems is possible only if it is associated with rhythmic oscillations from the olfactory bulb, dependent on nasal mechanical stimulation. We therefore consider the complex interactions between the modulation of the respiratory frequency, the training of voluntary top-down focused attention, and the specific breathing route involved, as a critical triad associated to meditative states of consciousness induced by breathing techniques. Further studies should investigate this hypothesis and the functional correlates involved in breathing techniques, adopting EEG and fMRI techniques, as well as new methods for phenomenological analysis of subjective experience.